Pancreatitis with Electrocardiographic Changes Mimicking Acute Myocardial Infarction - Paul Khairy; Pierre Marsolais (Canadian Journal of Gastroenterology)
A 64-year-old woman with mild acute pancreatitis presented with epigastric pain, nausea and vomiting while undergoing hemodialysis for chronic renal insufficiency. Serial electrocardiograms revealed new onset ST segment elevations in leads V2 to V4 mimicking an anterior myocardial infarction, followed by diffusely inverted deep T waves. No cardiac pathology was demonstrated by echocardiography or coronary angiography. A review of the literature and possible pathophysiological mechanisms of electrocardiographic changes in acute pancreatitis, such as metabolic abnormalities, hemodynamic instability, vasopressors, pericarditis, myocarditis, a cardiobiliary reflex, exacerbation of underlying cardiac pathology, coagulopathy and coronary vasospasm, are discussed.